Strategi Pemasaran UMKM Terez Collection di Sentra Rajutan Binong Jati Kota Bandung Jawa Barat - Siti Titta Partini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
UMKM Terez Collection have experienced a downward sales trend and very drastically after the Covid-19 pandemic. The aim of the research is to determine the Terez Collection's marketing strategy and the obstacles faced in increasing its sales value. This type of qualitative descriptive research uses a purposive sampling method. Data collection methods are observation, interviews and literature study. Data analysis involves data collection, reduction, presentation, drawing conclusions and verification. The market segment being worked on is teenage women aged from teens to adults, lower middle class. Meanwhile positioning has not been carried out and understood well. The research results show that the product in consumer perception has good quality in its class, is varied and meets consumer wants. The pricing strategy is quite good and competitive. The promotional strategy is still conventional so that the distribution channel is still one channel, namely conventional. The location of production and management of UMKM in production centers is an added value. Distribution is carried out through wholesalers and retailers. The obstacle faced is that the owner does not understand digital marketing well, and has not taken advantage of opportunities through product innovation. Suggestions for local governments to facilitate and encourage the return of the Binong Jati knitting center, to help facilitate financing for product innovation and training. Terez Collection is advised to increase knowledge and carry out digital marketing as an effort to expand the market.